Pharmacokinetic Study and Bioavailability of a Novel Synthetic Trioxane Antimalarial Compound 97/63 in Rats - Kushwaha, Hari Narayan (Hindawi Publishing Corporation, 2014)
Single dose pharmacokinetics study of 97/63 (IND191710, 2004), a trioxane antimalarial developed by Central Drug Research Institute, Lucknow, India, was studied in rats following intravenous and oral administration. Serum samples were analysed by HPLC-UV assay. Separation was achieved on a RP-18 column attached with a guard using acetonitrile : phosphate buffer (70 : 30% v/v) with UV detector at wavelength 244 nm. Serum samples were extracted with n-hexane. Two-compartment model without lag time and first-order elimination rate was considered to be the best fit to explain the generated oral and intravenous data. Method was sensitive with limit of quantification of 10 ng mL(−1). Recovery was >74%. Terminal half-life and area under curve (AUC) after administering single oral (72 mg kg(−1)) and intravenous (18 mg kg(−1)) doses were 10.61 h, 10.57 h, and 1268.97 ng h mL(−1), 2025.75 ng h mL(−1), respectively. After oral dose, 97/63 was rapidly absorbed attaining maximum concentration 229.24 ng mL(−1) at 1 h. Bioavailability of 97/63 was ~16%. The lower bioavailability of drug may be due to poor solubility and first-pass metabolism and can be improved by prodrug formation of 97/63.